Synthetic Studies towards Pyrido[1,2-a]azepine Stemona Alkaloids - Morgenstern, Martin; Mayer, Camilla; Pöthig, Alexander; Bach, Thorsten (Synthesis, 2022)
The carbon skeleton of the Stemona alkaloids stemokerrin and cochinchistemonine was assembled from three building blocks (a piperidine, a furan, and a tetronate). Key steps linking the fragments included a Stille cross-coupling (piperidine/furan) and an aldol-type addition of a tetronate. The furan served as a latent 1,4-difunctional compound which was converted into a γ-ketolactone by a type II photooxygenation. Attempts to construct the C12–C13 double bond of stemokerrin by a late-stage oxidation or by an elimination remained unsuccessful. The non-natural products dihydrostemokerrin and furostemokerrin were obtained instead.
Keywords: alkaloids; cross-coupling; diastereoselectivity; oxidation; pyridines; total synthesis